Navigating Delays: A Study on Diagnostic and Treatment Intervals in Nasopharyngeal Carcinoma Patients - Ezra, Moza Azzaria; Rafli, Rhandyka (http://dharmais.co.id/, 2026)
Background: Nasopharyngeal carcinoma (NPC) presents significant diagnostic and treatment challenges in Indonesia, where delays are common. This study aimed to describe patient characteristics, symptom profiles, diagnostic and treatment delays, and contributing factors.Methods: A cross-sectional study was conducted in October and November 2023, involving 67 NPC patients. Data were collected through a self-administered Google Form distributed through cancer survivor communities and oncology networks. The survey included demographic information, symptom history, treatment timelines, and contributing factors. Descriptive statistics were used to analyze the data. Results: Of the 67 patients, 62.7% were male, and the most common age group was 36–45 years. Most were diagnosed at stage IV (59.7%) and resided in West Sumatra (55.2%). The median diagnostic delay was 20 weeks, and the median time to first and second treatment was 6 weeks. Patient-related factors, such as lack of knowledge (77.6%), contributed to diagnostic delay, while healthcare-related factors (68.7%) caused treatment delays. Conclusions: NPC patients in this study experienced substantial diagnostic and treatment delays. Key contributing factors include limited symptom awareness, psychological barriers, and service access limitations. Efforts to reduce delays should focus on public education, improved healthcare infrastructure, and reducing financial barriers.